Software Framework For A Development Of Equivalent-Circuit Model - Mivalt, Filip (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
The paper describes a software for development of equivalent-circuit models and its parameters estimation on the basis of experimental data. The software engine contains set of features neccesary for impedance computing of any circuit composed of only linear, passive elements. Functions are implemented with regard to possibility of algorithm extension with voltage and current sources or active components. Software engine also contains features for evaluation of equivalent-circuit models and basic elements of artifficial intelligence as artifficial neural networks with basic learning method.
Keywords: Software engine; equivalent-circuit model; node voltage method; artifficial neural network